EXPLORING THE FACTORS AFFECTING PURCHASE BEHAVIOR OF ORGANIC FOOD: A STUDY ON DHAKA CITY - Miah, MD Qaium; Jim, Mahafizur Rahman (Finansha: Journal of Sharia Financial Management, 2024)
Organic food’s demand is expanding day by day as organic food is healthier and environmental-friendly compared to nonorganic food. The awareness of organic food also is rising in the Asia-pacific region. Consumers’ buying pattern of organic food has dramatically changed during the time. This study’s aim is to examine the predictors of purchase intention and consumer buying pattern of organic food in Dhaka, Bangladesh. Data was collected from 310 organic food consumers and SEM (structural equation modeling) was used to analyze the data thorough using Smart PLS. The findings of the study showed that self-identity is the most important predictor of purchase intention of organic food in Dhaka, Bangladesh, health consciousness is the 2nd most significant predictor, and attitude is the 3rd most important predictor. Purchase intention is found to mediate the relationship between self-identity, health consciousness, and attitude with purchase behavior. The predictive role of subjective norm, moral norm, environmental concern, and the moderating role of trust and purchasing power were not proven in this study. This study provides important insights about the organic food market in Dhaka, Bangladesh.